Intercropping drives plant phenotypic plasticity and changes in functional trait space - James Ajal; Lars P. Kiær; Robin J. Pakeman; Christoph Scherber; Martin Weih (Basic and Applied Ecology, 2022)
The relevance of intercropping, where two or more crop species are simultaneously grown on the same land space, is growing due to its potential for improving resource use and maintaining stable yields under variable weather conditions. However, the actual growth of intercropped species may differ resulting from the idiosyncratic effect of crop diversity, and with this, the realized benefits from intercrops are found to depend critically on the cultivar, species, management and environmental conditions. This study aimed to apply a trait-based approach, in which ecological niche spaces are defined through n-dimensional hypervolumes, to identify the contribution of species/cultivar, cultivation design (sole crop or intercrop) and management (low or high fertilization) to the trait diversity of four crop species, pea-barley and faba bean-wheat, when grown as sole crops and intercrops. Four traits were used as trait axes for the trait space analysis: canopy height, shoot biomass, tiller/node number, and grain yield. We found that trait spaces differed with crop species and cultivars, and whether they were grown as intercrops or sole crops. Trait spaces differed between high and low fertilization only for the cereals grown in the more productive site (i.e. Denmark). Species grown as intercrops had larger volumes than when grown as sole crops, as a result of trait plasticity. This response to intercropping was apparent in almost all the species grown in Sweden and Denmark, except for wheat in Denmark. The study demonstrated that individual species responded to intercropping compared to sole cropping through the plasticity of traits, which influenced the shape of the hypervolumes to divide up the trait space between the species. The findings are important in illustrating the plastic responses of arable crops, which are relevant for understanding the productivity of species grown in intercrops as compared to sole crops.